Gastrointestinal symbiont diversity in wild gorilla: A comparison of bacterial and strongylid communities across multiple localities - Bethan Mason; Klara J. Petrzelkova; Jakub Kreisinger; Torsten Bohm; Barbora Cervena; Emilie Fairet; Terence Fuh; Andres Gomez; Sascha Knauf; Ulrich Maloueki; David Modry; Matthew H. Shirley; et al. (Molecular Ecology, 2022)
Western lowland gorillas ( Gorilla gorilla gorilla ) are Critically Endangered and show continued population decline. Consequently, pressure is mounting to better understand their conservation threats and ecology. Gastrointestinal symbionts, such as bacterial and eukaryotic communities, are believed to play vital roles in the physiological landscape of the host. Gorillas host a broad spectrum of eucaryotes, so called parasites, with strongylid nematodes being particularly prevalent. While these communities are partially consistent, they are also shaped by various ecological factors, such as diet or habitat type. To investigate gastrointestinal symbionts of wild western lowland gorillas, we analysed 215 faecal samples from individuals in five distinct localities across the Congo Basin, using high‐throughput sequencing techniques. We describe the gut bacterial microbiome and genetic diversity of strongylid communities, including strain‐level identification of amplicon sequence variants (ASVs). We identified strongylid ASVs from eight genera and bacterial ASVs from 20 phyla. We compared these communities across localities, with reference to varying environmental factors among populations, finding differences in alpha diversity and community compositions of both gastrointestinal components. Moreover, we also investigated covariation between strongylid nematodes and the bacterial microbiome, finding correlations between strongylid taxa and Prevotellaceae and Rikenellaceae ASVs that were consistent across multiple localities. Our research highlights the complexity of the bacterial microbiome and strongylid communities in several gorilla populations and emphasizes potential interactions between these two symbiont communities. This study provides a framework for ongoing research into strongylid nematode diversity, and their interactions with the bacterial microbiome, among great apes.